Analysis of the dynamics of food security in the countries of the Eurasian Economic Union - Sergeyeva, Natalya; Evgrafova, Lyudmila; Dzhancharova, Gulnara; Ukolova, Anna; Kovaleva, Elena (Frontiers in Sustainable Food Systems, 2023)
The research is based on the methodology of export and import of agri-food products by the EAEU countries of the World Trade Center. The analysis of food security of the EAEU was carried out by the methods of descriptive statistics and related disciplines (econometrics, multidimensional statistical methods, mathematical modeling) and the index approach. As a result, we revealed that the mutual exchange of provisional goods of the EAEU countries is characterized by a steady upward trend. It was noted that increasing production volumes and joint international and Russian trade communications will help increase the macro-micro level of self-sufficiency in the key range of food products for both the EAEU states and the population in particular.